Political Feminism and Women's Representation in Public Policy in Indonesia - Bhakti Wiranti; Faizah Abdullah Latif; Imat Hibbatulloh; Hijriatu Sakinah; Moh. Wildan Hidayatullah (Mahkota Science Publishers, 2025)
This study aims to identify structural, cultural, and political factors that still hinder women in fighting for gender interests in the public policy arena. This study employs a qualitative research method using Critical Discourse Analysis (CDA) developed by Norman Fairclough, combined with intersectionality analysis from Kimberlé Crenshaw, and political representation theory from Hanna Pitkin to produce a comprehensive, critical, and contextually sensitive analysis of Indonesia's socio-political landscape. The findings state that it is now time for Indonesia to stop being satisfied with merely increasing the number of women in politics and start demanding real change—not just new faces, but bold moves that can dismantle patriarchal public policies, free women from co-optation, and promote the emergence of female leadership that dares to challenge, defend the oppressed, and demand substantive justice; political feminism must become the energy that forces the state and political parties to truly prioritise women's interests, not just use them as window dressing for democracy. To achieve this, a transformation of political culture, structural reforms, and the strengthening of women politicians' capacity are needed so that they can stand firm amid the whirlwind of political compromise and the still very strong pressure of masculinity.